2010
DOI: 10.1021/jo101871q
|View full text |Cite
|
Sign up to set email alerts
|

Dications of Benzylidenefluorene and Diphenylmethylidene Fluorene: The Relationship between Magnetic and Energetic Measures of Antiaromaticity

Abstract: Oxidation of m-and p-substituted benzylidene fluorenes to antiaromatic dications was attempted by electrochemical and chemical means. Electrochemical oxidation to dications was successful for benzylidene fluorenes with p-methoxy, p-methyl, p-fluoro, and unsubstituted phenyl rings in the 3-position; attempts to oxidize the m-substituted derivatives via electrochemistry were unsuccessful. Chemical oxidation with SbF 5 /SO 2 ClF gave the dication of 9-[(4-methoxyphenyl)methylene]-9H-fluorene cleanly; oxidation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…This work was extended to the formation of dications from substituted benzylidenefluorenes 19/20. 53 The relationship between calculated and experimental chemical shifts for the protons of 19, Z = OCH 3 , was good, as shown in Figure 1, which also supports the magnitude of NICS values calculated in the same way. Some researchers have concluded that the calculations of NICS for antiaromatic species give values that are abnormally large, but it is clear that the relationship of calculated and experimental chemical shift for the protons on the benzyl substituent are the same as for the fluorenyl systems, which cannot then be abnormally large.…”
Section: ■ Energetic Measures: Small Homo−lumo Gapssupporting
confidence: 79%
“…This work was extended to the formation of dications from substituted benzylidenefluorenes 19/20. 53 The relationship between calculated and experimental chemical shifts for the protons of 19, Z = OCH 3 , was good, as shown in Figure 1, which also supports the magnitude of NICS values calculated in the same way. Some researchers have concluded that the calculations of NICS for antiaromatic species give values that are abnormally large, but it is clear that the relationship of calculated and experimental chemical shift for the protons on the benzyl substituent are the same as for the fluorenyl systems, which cannot then be abnormally large.…”
Section: ■ Energetic Measures: Small Homo−lumo Gapssupporting
confidence: 79%
“…Interestingly, as a result of species that can reversibly hold and donate electrons, compounds 8 a-c demonstrated an amphoteric electrochemical behavior, relative to other simpler overcrowded polycycles recently reported. [16] Particularly, the formation of the cation radical produces a stable antiaromatic species as in the case of benzylidenefluorene systems described by Mills et al, [17] whereas the formation of the reduced species is due to two main driving forces: 1) A gain in aromaticity resulting from the formation of 14-and 22-pelectron systems, and 2) strain relief from the interaction of the protons of the fulvalene-like fragments. [18] In fact, the two fluorene moieties in the case of 8 a, b and the benzeneannulated moieties in 8 c (linked to the core by a double bond) are forced to be coplanar.…”
Section: Resultsmentioning
confidence: 99%
“…We anticipated that the electron-donating (destabilizing) group on the benzyl substituent would enhance the antiaromaticity of the dibenzotropylium anion just as electron-withdrawing groups on the benzyl substituent of the analogous benzylidene fluorene dications had enhanced the antiaromaticity of the fluorenyl system. 7 We observed instead the over-reduction of the desired dianion (1 2À ) to an unexpected tetraanion (1 4À ), which contains an aromatic dibenzotropylium trianion (Scheme 1). Of particular interest was our inability to observe the dianion in the 1 H NMR spectrum of the reaction mixture.…”
Section: Introductionmentioning
confidence: 85%